Encrusting offers protection against phytotoxic chemicals and maintains the physiological quality of sunflower (Helianthus annuus) seeds - Szemruch, Cyntia; Ferrari, Liliana (Seed Science Technolgy, 2013)
Precision planting of sunfl ower seeds is hampered by the large variability in size and shape. Seed encrusting, the application of layers of adhesive and inert material, has the potential to solve this problem. However, these layers could reduce the physiological quality of the seeds. The aim of this study was to evaluate the effect of encrusting on the germination and seedling growth of sunfl ower seeds, after encrusting and during storage. The treatments applied were: encrusted with talc, encrusted with carbonate, encrusted with talc + insecticide + fungicide, treated with insecticide, treated with fungicide and treated with insecticide + fungicide. Encrusting improves radicle emergence, without negatively affecting seedling percentage and growth rate. The dry weight of seedlings was signifi cantly higher in encrusted seeds. The germination percentage was stable for eight months in control, encrusted and treated seeds, with signifi cant reduction after that time. We verifi ed an adverse effect of insecticide + fungicide upon germination, but it seems that encrusting blocked the negative effect of pesticides on sunfl ower germination.
Keywords: Sunflower; encrusted; seed; radicle emergence